My lucky day - Kasza, Keiko (New York : G.P. Putnam's Sons, 2004)
When a young pig knocks on a fox's door, the fox thinks dinner has arrived, but the pig has other plans.
G1
Keywords: Pigs -- Fiction; Foxes -- Fiction